Psikologi Kegelapan: Membedah Konflik Batin Tokoh Utama Dalam Novel Rumah Tanpa Cahaya - Kurniawati, Heni; Handayani, Wuri; Faridah, Siti; Yayang Pamungkas, Onok (Universitas Tidar, 2025)
This study examines the psychology of the main character in the novel Rumah Tanpa Cahaya by Regita-Lenn Liu. The research aims to identify the psychological conflict experienced by the main character, Natta, through Sigmund Freud's personality theory (id, ego, superego) that illustrates the mental turmoil caused by family dynamics. The methodology used is hermeneutic qualitative analysis, focusing on symbolic and textual interpretation. The results of the analysis show that Natta experiences internal conflict between desire (id), reality (ego), and moral values (superego), especially in her relationship with her younger brother, Alie, who is ostracised by his family. This conflict shapes Natta's decisions, showing that the id has an important role in the positive actions she takes, despite going against her social environment. This study reveals that psychological elements in novels can provide an in-depth understanding of the complexity of characters and their impact on the storyline. The implication is that psychological analysis of literature helps readers understand personality dynamics in fictional narratives and their relevance to real-life conflicts.